SPARK MACHINING FOR STEEL SURFACES TO IMPROVE PAINT COATINGS QUALITY - Levchenko, Sergey; Ledovskykh, Volodymyr (Proceedings of National Aviation University (archive), 2016)
Spark machining of steel surfaces enhances the subsequent paint coatings adhesion and protective properties. These factors improvement was confirmed at the salt-spray chamber testing and by both adhesion to the surface and depth of corrosion penetration below the paint coating layer measurements.